Acalculous Cholecystitis in a Patient with Hepatocellular Carcinoma on Sorafenib. (23rd November 2010) - Sanda, Mariko; Tamai, Hideyuki; Deguchi, Hisanobu; Mori, Yoshiyuki; Moribata, Kosaku; Shingaki, Naoki; Ueda, Kazuki; Inoue, Izumi; Maekita, Takao; Iguchi, Mikitaka; Yanaoka, Kimihiko; Oka, Masashi; et al.
Abstract : A 67-year-old woman with compensated cirrhosis type B associated with hepatocellular carcinoma was started on sorafenib for multiple pulmonary metastases. The patient developed right upper quadrant pain and high fever 4 weeks later. Imaging revealed marked enlargement of the gallbladder without calculi. Following percutaneous transhepatic gallbladder aspiration, her symptoms resolved, but the gallbladder remained enlarged. Laparoscopic cholecystectomy was performed. Arteriolar occlusion with intimal thickening in the muscular layer of the gallbladder was seen sporadically. The fact that this patient had no risk factors for acalculous cholecystitis suggested that the cholecystitis resulted from ischemia, implying a strong causal relationship with sorafenib.